2017 26th IEEE International Symposium on Robot and Human Interactive Communication (RO-MAN) 2017
DOI: 10.1109/roman.2017.8172278
|View full text |Cite
|
Sign up to set email alerts
|

Would you like to sample? Robot engagement in a shopping centre

Abstract: Nowadays, robots are gradually appearing in public spaces such as libraries, train stations, airports and shopping centres. Only a limited percentage of research literature explores robot applications in public spaces. Studying robot applications in the wild is particularly important for designing commercially viable applications able to meet a specific goal. Therefore, in this paper we conduct an experiment to test a robot application in a shopping centre, aiming to provide results relevant for today's techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
(50 reference statements)
2
10
0
Order By: Relevance
“…For example, customers gave the following reasons for accessing the QR code: “The robot was cute and stopped me in my tracks,” and “Sota recommended it to me.” They also gave answers for not accessing the code such as, “The robot suddenly started doing business.” This result suggests that the customers’ attention was focused on the robot and not on the content that the robot introduced. Similar results were confirmed in the studies of Song et al (2021) and Tonkin et al (2017) , and this experiment also reaffirmed the major challenges of proactive service delivery by robots.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…For example, customers gave the following reasons for accessing the QR code: “The robot was cute and stopped me in my tracks,” and “Sota recommended it to me.” They also gave answers for not accessing the code such as, “The robot suddenly started doing business.” This result suggests that the customers’ attention was focused on the robot and not on the content that the robot introduced. Similar results were confirmed in the studies of Song et al (2021) and Tonkin et al (2017) , and this experiment also reaffirmed the major challenges of proactive service delivery by robots.…”
Section: Discussionsupporting
confidence: 85%
“…Still, the offsetting will not make a huge difference in performance. The results of the study by Tonkin et al, 2017 also showed that the maximum performance in both robot and staff conditions was the same. At least for the task of outbound customer service, as in this experiment and Tonkin’s study, we could not find any significant difference in performance between working remotely with a robot and working locally, and H1 was not denied.…”
Section: Discussionmentioning
confidence: 71%
“…Sample tasting has been shown to be effective in promoting sales [ 24 ], where the psychological effect called the norm of reciprocity affects the customer, who feels that something must be returned after receiving something from another person. In addition, a study has been conducted in which tasting was performed using a robot in a field experiment [ 25 ]. In the study, the authors compared the abilities of a robot and humans to successfully advertise sample tastings to customers in large shopping centers, and demonstrated that the robot was more effective than humans.…”
Section: Modeling Of the State-transition In A Customer–robot Intementioning
confidence: 99%
“…Bennewitz et al [4] present a robotic system, called Alpha, that makes use of visual perception, sound source localisation, and speech recognition, to detect, track and interact with potential users. Tonkin et al [27] conduct experiments to validate a robot system in a shopping centre. In their work, they compare the performance of a robot and a human in promoting food samples and analyse the effects of the type of engagement used to achieve this goal.…”
Section: Related Workmentioning
confidence: 99%